Evaluating and pricing lanes in the truckload motor freight industry. (23rd July 2009) - Madden, Timothy; Russell, Robert A.
In this article, we develop methods for evaluating and pricing lanes in the truckload motor freight industry. An optimisation-based simulation approach is used to suggest lane prices in the carrier's existing network and to examine various strategic scenarios. Two efficient heuristics are developed which provide relatively accurate prices and facilitate implementation. Computational results are reported and the pricing methods are compared to actual carrier prices and prices from a commercial data service.